2002
DOI: 10.1007/s12031-002-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts play an important role in Aβ biogenesis by regulating the β-secretase pathway

Abstract: The Alzheimer's amyloid beta protein (A beta) precursor (APP) is proteolytically cleaved by beta-secretase to N- and C-terminal fragments sAPPbeta and CTFbeta, respectively. Subsequently, CTFbeta is cleaved by gamma-secretase to generate A beta. We previously showed that the levels of secreted A beta and sAPPbeta were significantly reduced upon removal of glycosylphosphatidylinositol (GPI)-anchored proteins from either primary brain cells or Chinese hamster ovary cultures. The results indicated that GPI-anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 14 publications
3
61
0
2
Order By: Relevance
“…Many factors besides actual BACE1 levels have been proposed to regulate b-secretase activity, and may be important in further understanding the functional relationship between BACE1, and the increased V max for the enzyme detected in this study in AD. These include: heparan sulphate proteoglycans [45,46], cholesterol [47,48] lipid rafts [36,37,49], reticulon family members [50,51] and PAR-4 [52]. Changed V max in the presence of unchanged K m may reflect the loss of a non-competitive inhibitor of b-secretase activity in AD brain, and increased V max for b-secretase has been observed with BACE1 dimerisation [53].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors besides actual BACE1 levels have been proposed to regulate b-secretase activity, and may be important in further understanding the functional relationship between BACE1, and the increased V max for the enzyme detected in this study in AD. These include: heparan sulphate proteoglycans [45,46], cholesterol [47,48] lipid rafts [36,37,49], reticulon family members [50,51] and PAR-4 [52]. Changed V max in the presence of unchanged K m may reflect the loss of a non-competitive inhibitor of b-secretase activity in AD brain, and increased V max for b-secretase has been observed with BACE1 dimerisation [53].…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of M2 ED Is Influenced by Cell Surface GPIanchored Proteins-It has been shown that the removal of GPI-anchored cell surface proteins reduced the endocytosis of cellular expressed native memapsin 2 (19). We therefore sought to determine if the same effect is also seen for exogenously added M2 ED .…”
Section: Endocytosis Of Memapsin 2 (␤-Secretase) Ectodomainmentioning
confidence: 98%
“…This interaction apparently serves to package memapsin 2 into clathrin-coated vesicles for transportation in the endocytic or/and recycling pathways (17,18). Being located in the lipid raft at the plasma membrane (19,20), memapsin 2 endocytosis is influenced by other components having direct or indirect contact with the protease. Such components include the glycosylphosphatidylinositol (GPI)-anchored proteins (19,36), scramblase (21), heparan sulfate (22), and cholesterol (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the enzymatic activity of b-and c-secretases is cholesterol-dependent (16,17), it is likely that the production of Ab reflects a biological response to the increased cholesterol availability.…”
Section: Cellular Cholesterol and Amyloidogenesismentioning
confidence: 99%